Role of PI3K/Akt/mTOR pathway in mediating endocrine resistance: concept to clinic - Skolariki, Aglaia; D’Costa, Jamie; Little, Martin; Lord, Simon (Exploration of targeted anti-tumor therapy, 2022)
The majority of breast cancers express the estrogen receptor (ER) and for this group of patients, endocrine therapy is the cornerstone of systemic treatment. However, drug resistance is common and a focus for breast cancer preclinical and clinical research. Over the past 2 decades, the PI3K/Akt/mTOR axis has emerged as an important driver of treatment failure, and inhibitors of mTOR and PI3K are now licensed for the treatment of women with advanced ER-positive breast cancer who have relapsed on first-line hormonal therapy. This review presents the preclinical and clinical data that led to this new treatment paradigm and discusses future directions.